Comparison of SSS-CN and PHQ-15 in the evaluation of patients with suspected psychological disorders in cardiovascular medicine - Fu, Yan; Lin, Qiuzhen; Xiang, Qunyan; Wen, Xingyu; Liu, Ling (Frontiers in Psychology, 2023)
Aims Somatic Symptom Scale-China (SSS-CN) has been applied to assess the presence and severity of somatization symptom disorders (SSD) in Chinese patients. However, there was no study comparing SSS-CN with Patient Health Questionnaire-15 (PHQ-15). The aim of this study was to compare the consistency of the SSS-CN with the PHQ-15 in evaluating SSD in patients with suspected psychological disorders in cardiovascular medicine and to explore the relationship between scores on the two SSD self-rating scales and scores on self-rating scales for anxiety or depression. Methods In this study, 1,324 subjects were enrolled by using a “three-question method.” Then, they completed four self-assessment scales, i.e., SSS-CN, PHQ-15, Patient Health Questionnaire-9 (PHQ-9), and General Anxiety Disorder-7 (GAD-7), in turn. The ability of SSS-CN to diagnose SSD was analyzed by the receiver operating characteristic (ROC) curve, and the area under the curve (AUC) value, sensitivity, and specificity were calculated. Reliability analysis was performed with the Kappa statistic to determine consistency between SSS-CN and PHQ-15. The relationship between two qualitative variables was analyzed by Spearman correlation analysis. Results The proportions of SSD evaluated by SSS-CN and PHQ-15 were 83.2 and 87.0%, respectively. SSS-CN score was significantly correlated with PHQ-15 one (r = 0.709, p < 0.001). The AUC of the SSS-CN for the diagnosis of SSD was 0.891, with a high sensitivity and acceptable specificity. There was a moderate agreement between SSS-CN and PHQ-15 in assessing SSD, with a Kappa value of 0.512. Anxiety and/or depression were detected in about 70% of patients with SSD. There was significant correlation between the score of each SSD scale and that of GAD-7 or PHQ-9 (SSS-CN: r = 0.614 or 0.674; PHQ-15: r = 0.444 or 0.582, all p < 0.001). In addition, the SSS-CN score was more closely correlated with the GAD-7 or PHQ-9 score than the PHQ-15 score, and a higher proportion of patients with anxiety or depression was detected in those with moderate and severe SSD evaluated by SSS-CN. Conclusion The SSS-CN could be one of the ideal scales for the rapid screening of patients with suspected psychological disorders in cardiovascular medicine.